Mexico : Technology, Wages and Employment, Volume 2. Technical Papers - World Bank (Washington, DC, 2013)
The report examines two components of new technology adoption by Mexican manufacturing firms. First, it questions which firms, under what circumstances, and performance adopt such technology. To measure performance, productivity wages, and net employment of a firm were used, leading to further questions on whether technological change helps workers - of a certain skill level - disproportionately. Second, it argues that adoption of new technologies happens under the right circumstances, and further reviews which are the firms, and circumstances surrounding the choice of technology. The analysis is based on data from the National Survey of Employment, Wages, Technology and Training (ENESTYC), and the National Industrial Survey (EIA) for 1992, 1995, and 1999. Results largely suggest that performance (including statistics, and measures on job creation, and/or job dislocation), is superior with technology adoption, though it does not imply performance increases in all firms. Rather, the effects of technology vary depending on location, and size of enterprise. Nonetheless, investments in human capital - training in conjunction with technology adoption - increases productivity benefits. In addition, the likelihood for new technologies, also varies markedly by time period, and, the complexity of the technology correlates both with the size, and skill levels of a firm's work force. Policy recommendations include widespread technology know-how, facilitating inter-firm linkages, supported by both government financing to encourage a competitive business environment, and by a continued increase in research and development funding, public as well as private funding.